Fortification of traditional tapioca "pancakes" from the Brazilian northeast with microencapsulated carrot carotenoid. (December 2021) - Landim Parente, Gisleânia Dourado; Nunes de Melo, Bruno Davinci; Albuquerque de Souza, Jaciel; da Conceição, Marta Maria; Ubbink, Job; Mattos Braga, Ana Luiza
Abstract: The feasibility to fortify traditional Brazilian cassava gum and tapioca "pancakes" with carotenoid from carrots was investigated, based on the premise that the process should be applicable as a social technology. Microparticles enriched in carotenoids were prepared by concentrating carrot juice solids using complex coacervation of whey protein isolate and gum arabic in the weight ratio of 1.5:1, and co-dried with cassava starch. Carotenoid content and stability during product application were analyzed for the microparticles and for two product applications: fortified cassava gum, and fortified tapioca "pancakes". The results showed that complex coacervation can be applied instead of conventional technologies to concentrate carrot juice, resulting in a yield of more than 90% of the initial carotenoid content. The further starch co-drying of this material resulted in a microparticle that retained 79% of initial carotenoid content. Low levels of carotenoid loss (22%) were observed upon preparing tapioca "pancakes" using the fortified cassava gum. The instrumental textural properties of the tapiocas were similar for products fortified with microparticles or by direct carrot juice addition. Furthermore, the use of carotenoid in dry powder form facilitates handling and dosing in artisanal and industrial settings and ensure to target the daily intake. Highlights: Complex coacervation was combined to tapioca starch for carotenoid encapsulation. A unique starch-based product rich in carrot carotenoids was developed. Addition of carotenoid microparticles to tapioca ensure to target vitamin A RDI. Microparticles did not influence tapioca "pancakes" overall textural properties. Carotenoids loss in products during storage and under heat was lower than 30%.